2020
DOI: 10.3171/2020.5.focus20169
|View full text |Cite
|
Sign up to set email alerts
|

The association between lower Hounsfield units on computed tomography and cage subsidence after lateral lumbar interbody fusion

Abstract: OBJECTIVEOne vexing problem after lateral lumbar interbody fusion (LLIF) surgery is cage subsidence. Low bone mineral density (BMD) may contribute to subsidence, and BMD is correlated with Hounsfield units (HUs) on CT. The authors investigated if lower HU values correlated with subsidence after LLIF.METHODSA retrospective study of patients undergoing single-level LLIF with pedicle screw fixation for degenerative conditions at the University of California, San Francisco, by 6 spine surgeons was performed. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 28 publications
2
56
0
3
Order By: Relevance
“…Biomechanical deteriorations initially trigger surgical segment complications. [6][7][8] Relations between screw positions and biomechanical environments have been widely reported. [9][10][11] This study has numerically investigated the effects of screw insertional position changes, and biomechanical indicators related to surgical segment complications (ie, cage subsidence, non-union, segmental instability, and fixation failure) have been computed and recorded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomechanical deteriorations initially trigger surgical segment complications. [6][7][8] Relations between screw positions and biomechanical environments have been widely reported. [9][10][11] This study has numerically investigated the effects of screw insertional position changes, and biomechanical indicators related to surgical segment complications (ie, cage subsidence, non-union, segmental instability, and fixation failure) have been computed and recorded.…”
Section: Discussionmentioning
confidence: 99%
“…2,5 Biomechanical deteriorations initially trigger these complications. [6][7][8] Studies reported that screw insertional positions and trajectories would affect the local biomechanical environment. [9][10][11] radiography guidance.…”
Section: Introductionmentioning
confidence: 99%
“…Some groups have reported that HU values may serve as an assessment of osteoporosis, given the moderate correlation between HU values and osteoporosis [ 37 , 38 , 39 ]. HU values have also evaluated studies of LLIF cage subsidence [ 40 , 41 ]. It was shown that the decrease in the HU value of preoperative CT correlates with the severity of cage subsidence after LLIF.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical settings, aBMD is compared to a young reference cohort of the same ethnic background and sex, generating a T-score. The International Society of Clinical densitometry (ISCD) defines osteoporosis in adults as a T score ≤2.5, representing 2.5 standard deviations below the young reference mean value ( 69 ). Another score reported from DXA measurements is the Z-score.…”
Section: Bone Density and Imaging - 2dmentioning
confidence: 99%